Opinion of WTP in Village Fund Management Accountability at the APIP Inspectorate of East Bolaang Mongondow Regency - Devo Sucita Lokiman; Driana Leniwati; Nazaruddin Malik (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research aims to analyze the accountability of village fund management and the role of supervision in realizing good village financial governance. The main problem in this study is the lack of optimal transparency, human resource capacity, and political intervention that affects the quality of village fund management. This study uses a descriptive qualitative approach with a case study method, with data collection techniques through interviews, observations, and documentation. Data analysis was carried out using an interactive model which included data reduction, data presentation, and conclusion drawn. The results of the study show that normatively village fund management has referred to the principles of Stewardship Theory and Good Governance, but the implementation is still not optimal. The main problems found include lack of transparency of information to the community, changes in programs that are not communicated openly, limited competence of village officials, and indications of nepotism practices in the distribution of aid. In addition, the role of the Government Internal Supervisory Apparatus (APIP) as an internal supervisor has run through the function of coaching and supervision, but its effectiveness still faces various obstacles. On the other hand, the quality of financial statements that have implications for the Fair Without Exception (WTP) opinion is greatly influenced by the internal control system and asset management. Thus, it is necessary to strengthen the capacity of human resources, increase transparency, and optimize supervision to realize accountable and public-interest-oriented management of village funds.